Analysis of Work Engagement, Organizational Culture and Loyalty to Employee Performance with Sustainability Strategy as Intervening Variables at PT Pelindo Multi Terminal - Deni Spartan; Kholilul Kholik; Yohny Anwar (Utan Kayu Publishing, 2025)
This study aims to analyze the influence of work engagement, organizational culture, and work loyalty on employee performance with sustainability strategy as an intervening variable at PT Pelindo Multi Terminal Belawan. The design of this study uses a quantitative method with a descriptive approach. The research population is all permanent employees totaling 170 people. The sample was determined using the Slovin formula with an error rate of 10%, so that a sample of 63 respondents was obtained. The sampling technique used is probability sampling with a simple random sampling approach. The data collection technique was carried out through a questionnaire based on the Likert scale. The collected data was analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS software. The results of the study show that work loyalty, followed by organizational culture, has also been proven to have a significant effect on employee performance. Organizational culture and work engagement have proven to have a positive and significant influence on sustainability strategies, showing that strong organizational values and high employee involvement are able to encourage the implementation of green port initiatives at PT Pelindo Multi Terminal. However, research found that work engagement had no significant effect on employee performance directly, and work loyalty had no significant effect on sustainability strategy. The most important finding is that sustainability strategies do not have a significant effect on employee performance and are not able to play a role as an effective intervening variable in mediating the influence of organizational culture, work loyalty, and work engagement on employee performance